2017
DOI: 10.1186/s12981-017-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six methods to estimate adherence in an ART-naïve cohort in a resource-poor setting: which best predicts virological and resistance outcomes?

Abstract: BackgroundIncomplete adherence to antiretroviral therapy (ART) results in virologic failure and resistance. It remains unclear which adherence measure best predicts these outcomes. We compared six patient-reported and objective adherence measures in one ART-naïve cohort in South Africa.MethodsWe recruited 230 participants from a community ART clinic and prospectively collected demographic data, CD4 count and HIV-RNA at weeks 0, 16 and 48. We quantified adherence using 3-day self-report (SR), clinic-based pill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 39 publications
3
60
1
1
Order By: Relevance
“…The median age was 33 years, 73.6% of participants were male and 73.6% of participants were Han Chinese. The median (IQR) body weight was 60 (54, 67) kg, and the median body mass index was 21 (20,24) kg/m 2 . The proportions of patients with HBV and HCV coinfection were 10.3% and 2.4% respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…The median age was 33 years, 73.6% of participants were male and 73.6% of participants were Han Chinese. The median (IQR) body weight was 60 (54, 67) kg, and the median body mass index was 21 (20,24) kg/m 2 . The proportions of patients with HBV and HCV coinfection were 10.3% and 2.4% respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…In China, mobile phone-based SMS reminders are reported to be acceptable and useful in establishing antiretroviral adherence routines [29]. In South Africa, adherence measured by a real-time monitoring technology emerged as one of the best predictors of antiretroviral drug resistance and virological failure [30]. In the same setting in Uganda, a mobile adherence monitoring intervention composed of real-time adherence technology and SMS reminders was reported to be acceptable [19] and to improve adherence to antiretroviral therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Each time the device is opened, a signal is sent to a server in Cape Town, South Africa for recording and access. In previous studies, Wisepill devices have demonstrated feasibility, acceptability, construct validity, and have been found to predict loss of viral suppression [2729]. Participants were instructed to place inside the device the medication that was most difficult to take or the one taken most frequently if they were unable to fit their full medication regimen into Wisepill.…”
Section: Methodsmentioning
confidence: 99%